PRIMARY CLOSURE OF PRESSURE ULCERS REVISITED - Kumar, P; Bhaskara, K G; Chittoria, R (Indian Journal of Plastic Surgery, 2000)
A total of 20 paraplegic patients with pressure ulcers under this study constituted of ten ischial, eight trochanteric and two sacral sorES. Basic principles of conservative management laid down were strictly followed. After excision of the ulcers, the wounds were primarily closed. Maximum size of the pressure ulcer under this study was 10 × 8 cm.Five patients lost to follow up. Remaining fifteen patients were followed for 6 months to 5 years, and in one patient recurrence was noticed. The most common complication noticed during the study was infection (20%) followed by partial wound dehisence (15%). Recurrence was noticed in one case.
Keywords: Pressure ulcer; Primary closure